Orthodontic cements induce genotoxicity and cytotoxicity in mammalian cells in vitro - Fernanda Angelieri; Renata P Joias; Eduardo Bresciani; Juliana Noguti; Daniel A Ribeiro (Wolters Kluwer Medknow Publications, 2012)
Background: This study assessed the genotoxic and cytotoxic potential of three different glass ionomer cements used in Orthodontics (Vidrion C, OptiBand, and Band-Lok). Materials and Methods: The tested cements were exposed in vitro to mouse fibroblast cells for 1 h at 37°C. The genotoxicity and cytotoxicity were evaluated by means of the single cell gel (Comet Assay) and the trypan blue exclusion test, respectively. All data were assessed by the Kruskal-Wallis non-parametric test, followed by Dunn's test. P < 0.05 was considered for statistical significance. Results: Significant statistically differences (P < 0.05) in cytotoxicity were observed for both Vidrion C powder and liquid at the tested concentrations, with exception to the group presenting the lowest powder concentration. OptiBand similarly presented induced cellular death at the highest tested concentration for paste A (P < 0.05). Band-Lok paste B was also able to induce cytotoxicity at the highest tested concentration. Regarding the comet assay, Band-Lok paste B and OptiBand paste A resulted in increased DNA injury (P < 0.05). Conclusion: The obtained results support the thought that some glass ionomer cement components present both genotoxic and cytotoxic effects when in high concentrations. Since DNA damage and cellular death are important events during oncogenesis, this study represents relevant contribution to estimate the real risks induced by these materials upon cellular systems.